Pembelajaran Tari Melinting Menggunakan Metode Demonstrasi dan Drill pada Kegiatan Ekstrakurikuler di SMA Negri 1 Way Jepara - Afrida Yeni, Agnes Agustini; Haerudin, Deden; Kusumawardani, Dwi (Jurnal Pendidikan Tari, 2022)
This research is abouth education with demonstration and drill methods of extracurricular activities. The purpose of this research is for describe education interaction process of melinting's dance. This research happened because there are advantages and disadvantages in using demontration and drill methods. This research conducted with qulitative methology and data collection by using observation, interview, and literature review. Data is analyzed through the process of data reduction, data persentation, and verification. Then, data is tested for it is credibility by using triangulation method. The result show how the demontration and drill methods in melinting's dance for extracurricular acrivities in high school and has advantage for teacher and student interaction. The result also for education, because teacher plays a role in education. But, it also has weakness in optmizing interaction between teacher and student.